(3HZjI GdWGdH aj eYQaI GdeaQhV hGdhGLHs - (3GdMdj, GdLfGLj, GdfLaj, ef Bd cGTa GdZWGA, LYaQ Hf NVQ Hf TdGd, J (B1227 (3g`s
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg GdPj GSS bhGYO GdCMcGe hQaY OYGFe GdESdGe (B... (3hbO QJHJgG Ydi KdGKI eWGdH, GdChd aj CUhd GdEjeGf hjdRe GdYde HgG Yf GdOdjd HWQjb GdYde hGdjbjfs
(3BNQgG (B:s
(3BNQgG(B: (3GdaUd GdKGdK EfeG jLH GdUhe Ydi GdHGdZ GdYGbd GdUMjM GdMGVQ Ch eG aj Mceg GdNGdj GdMjV Ch GdfaGS adG jLH Ydi GdUHj hGdeLfhf EdG Cf jcedG bHd GdaLQ Ohf eG HYOgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B2: 124s
(3GdPQjYI, L (B3: 74s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis